Analisis Pengembangan E-Government pada Layanan Administrasi Pemerintahan (Studi pada “SURADI” di Dinas Komunikasi dan Informasi Kota Malang) - Budi Ratnasari, Mega Oktavia; Noor, Irwan; Hidayati, Firda (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study aims to analyze the development of e-government on an electronic-based government system. The object of this research is the development of SURADI as a form of government administration service that applies the concept of e-government in the Communication and Information Office of Malang City. So, this study will look at the extent to which SURADI as a form of e-government development is analyzed based on the theoretical concept of e-government development. The elements of e-government development include support, capacity, value, willingness, and local culture. The results of this study indicate that the development of SURADI by the Department of Communication and Information as an online-based government system for government administration services in Malang City is going well by using the five elements of e-government development well. As for the supporting factors and inhibiting factors in the implementation of the development of SURADI, it is necessary to take steps to improve and improve the system development based on five elements in accordance with the available supporting factors.